2011
DOI: 10.3945/jn.110.132332
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Are Associated with Different Indexes of Adiposity and Obesity in an Urban Mexican Population1,2

Abstract: Our objective was to evaluate the relationships between dietary patterns and obesity, abdominal obesity, and high body fat proportion (measured by dual-energy X-ray absorptiometry; >25% in men and >35% in women) in an urban Mexican population. We conducted a cross-sectional analysis with the baseline data from 6070 men and women aged 20-70 y participating in the Health Workers Cohort Study, including information on participants' socio-demographic status and physical activity collected via self-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 38 publications
7
42
0
4
Order By: Relevance
“…Prior research from Mexico has identified an association between specific dietary patterns and the presence of obesity (12,13), metabolic syndrome (9), insulin resistance (14), and gastric cancer (15). However, to date there are no reports on the relationship between dietary patterns and intake of specific nutrients, in Mexico or elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research from Mexico has identified an association between specific dietary patterns and the presence of obesity (12,13), metabolic syndrome (9), insulin resistance (14), and gastric cancer (15). However, to date there are no reports on the relationship between dietary patterns and intake of specific nutrients, in Mexico or elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Factors with an eigenvalue above 1.5 were retained after the assessment of eigenvalues, graphic analysis and interpretability. Each factor was defined by a subset of at least 5 food groups with an absolute ≥ 0.2 load factor (considering that ≥ 0.2 load factors contributed significantly to the dietary pattern) as suggested in previous analyses (9,(13)(14)(15)22). The factor scores for each dietary pattern were estimated by adding the consumption of the food groups weighted by their load factor, and each participant received a factorial score for each of the identified patterns.…”
Section: Dietary Pattern Derivationmentioning
confidence: 99%
“…First, dietary pattern analysis should be interpreted with caution because, although at least two major patterns ("healthy" or "prudent" and "unhealthy or "western") have commonly emerged in different populations, 7,19,28,29,34 their specific composition depends on geographical, cultural, socioeconomic and ethnic status, and is influenced by methodological variation (including sampling, food grouping, number of variables used in factor analysis, number of factors and the rotation employed). Further, the three major dietary patterns identified in our study explained only 20.4% of the total variance in the SFFQ 7 In the present study, two 24DRs were used as comparison method; therefore, the estimate of intake may have been closer to true intake if we had collected more days of food consumption.…”
Section: Artículo Originalmentioning
confidence: 99%
“…Details of the food groupings used to derive the dietary patterns are described elsewhere. 28,29 Briefly, as explained in Denova and colleagues, 28 the basis for placing a food item in a certain food group was the similarity of nutrients. Some groups were defined according to the amount of sugar added (e.g.…”
Section: Food Groupingmentioning
confidence: 99%
“…Studies have shown the association between unhealthy eating patterns and both general and abdominal obesity and identified mainly the consumption of red meat, whole dairy, processed foods, refined grains, high amounts of trans fat, and simple carbohydrates as predictors of such metabolic disorders [5][6][7]. However, consumption of healthy foods such as fruit, vegetables, low-fat meats, high-fiber diets, and low-glycemic index foods has been linked to the protective effect against general and central obesity [7,8] .…”
Section: Introductionmentioning
confidence: 99%